P2SK Law and Islamic Banking SDI Development: A Sharia Economic Legal Perspective - Wahidatur Rosyidah; Andi Fariana; Prameswara Samofa Nadya Iskand; R. Adelina Fauzie (International Journal of Emerging Issues in Islamic Studies, 2025)
Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK) represents the Government’s commitment to strengthening the national financial system, including the development of human resources in the financial sector. However, the implementation of this mandate poses a specific challenge for Islamic banking, as its human resources (Sumber Daya Insani/SDI) are required not only to meet technical and professional standards, but also to embody Islamic values that underpin sharia-based financial operations. Existing regulations on SDI development in the financial sector tend to adopt a general and technocratic approach, leaving a regulatory gap in accommodating the distinctive characteristics of Islamic banking SDI. This research aims to examine how the P2SK Law and its related regulations govern SDI development in Islamic banking and to formulate an SDI development model that is normatively aligned with sharia principles while remaining compliant with the prevailing legal framework. Employing doctrinal legal research with a statutory approach, this study analyzes relevant laws and regulations, supported by Ibn Khaldun’s theory of human development and the perspective of Sharia economics as a branch of political law. The findings propose an SDI development model for Islamic banking that integrates technical competence, professional integrity, and spiritual intelligence rooted in tawhid and akhlaq, and demonstrates its compliance with the P2SK Law and relevant OJK regulations. Theoretically, this research contributes to the integration of Islamic human resource concepts into legal scholarship, while providing a practical normative reference for regulators and Islamic banking institutions in formulating SDI development policies.